Keabsahan Salinan Akta Atas Minuta Akta Yang Disimpan Sebagai Protokol Yang Belum Ditanda Tangani Notaris - Sri Giyanthi, Putu Indri; Apryani, Ni Wayan Ella (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024)DO - 10.24843/10.24843/AC.2024.v09.i02.p13, 2024)
The purpose of writing this article is to analyze the legal force of the copy of the deed on the minuta deed that has not been completely signed by the Notary and the legal consequences of the Notary Public issuing a copy of the deed on the minuta deed that has not been signed by the Notary related to the precautionary principle. This study uses normative legal writing methods with statutory and conceptual approaches. The source of legal materials used, primary legal materials consisting of laws and regulations and secondary legal materials consisting of books, journals and articles relevant to the problem to be studied. The results of this study show that the legal force of a copy of a deed whose request has not been completely signed by a Notary should not be issued and the legal consequences for Notaries can be prosecuted to the Court with civil, criminal or administrative threats because it can be said to violate Article 16 paragraph (1) letter m, Article 44 paragraph (1) and Article 16 paragraph (1) letter a of the Notary Position Law .